2021
DOI: 10.26803/ijlter.20.9.3
|View full text |Cite
|
Sign up to set email alerts
|

International Graduate Students’ Experiences of English as a Medium of Instruction (EMI) Courses in a Korean University

Abstract: Owing to to the internalization of higher education, many universities in East Asia provide English as a medium of instruction (EMI) courses for international students. However, previous studies may not have strategically explored the perception of EMI courses for graduate programmes. Recognizing the gap in the literature, this study specifically focused on international graduate students' experiences of EMI courses in a Korean university. By implementing a mixed-method design, this study explored English lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Both positive and negative beliefs have been reported. For example, learners believe that English-Medium Instruction (EMI) can enhance their English language proficiency (Lee et al, 2021;Macaro & Akincioglu, 2018;Rowland & Murray, 2020). Conversely, other studies have reported that while students are satisfied with EMI classes, they do not believe that such instruction significantly improves their English language proficiency (Kym & Kym, 2014).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Both positive and negative beliefs have been reported. For example, learners believe that English-Medium Instruction (EMI) can enhance their English language proficiency (Lee et al, 2021;Macaro & Akincioglu, 2018;Rowland & Murray, 2020). Conversely, other studies have reported that while students are satisfied with EMI classes, they do not believe that such instruction significantly improves their English language proficiency (Kym & Kym, 2014).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Most current EMI studies focus primarily on students at the undergraduate level, but postgraduate students differ from undergraduates in many aspects, including age, educational background, work experiences, learning styles, attitudes, and language proficiency levels [20,21]. The length of undergraduate studies is around three to four years, while a typical postgraduate programme lasts only one to two years, giving students an intensive curriculum and high academic demands [1,11].…”
Section: Emi At the Postgraduate Levelmentioning
confidence: 99%
“…A plethora of literature has investigated students' experiences and perceptions of EMI in tertiary education [10,19,24,25]. Generally, students show positive attitudes toward the adoption of EMI [20,25,26]. However, in Zhang and Pladevall-Ballester's study [25], it was found that students' attitudes changed over time throughout the EMI learning process, and the challenges they faced could negatively affect their experiences.…”
Section: Students' Experiences and Perceptions Of Emimentioning
confidence: 99%
“…According to Byun et al (2011) and Tong and Shi (2012), the learning content in their EMI subjects appears to be very difficult for students to understand and master, which causes their growing anxieties in their EMI context. In addition, EMI courses have also brought students considerable challenges in lecture comprehension, textbooks or course materials available, tests and exams, interactions and discussion in the classrooms, lecturers' proficiency in language and EMI (Chang, 2010;Al-Bakri's, 2013;Lasagabaster et al 2018;Tamtam et al, 2012;Lee, Davis & Li, 2021).…”
Section: Introductionmentioning
confidence: 99%